SENSE, REFERENCE, DAN GENRE NOVEL MERAHNYA MERAH KARYA IWAN SIMATUPANG (ANALISIS HERMENEUTIKA PAUL RICOEUR) - Aslan Abidin (Universitas Negeri Makassar, 2016)
Abstract. Sense, Reference, and Genre Merahnya Merah Novel by Iwan Simatupang (Hermeneutic Paul Ricoeur analysis). Paul Ricoeur's her meneutic theory call edautonomousmeaningfulliterarytextsofthe writers' intentions. Textis notonly are flection of the author's psychological and sociologi calcon text in which the tex twas produced. Meaning of the text can be traced from his relationship with the text bythe meaning (sense), the relationship with thetext-external world formed byreference(reference), can also be determined by the meaning of a literary genre. The text in the novel Merahnya Merah, Iwan Simatupang work, shows that poetic sense of meaning by reference is indeed possible. Dialectic between sense with reference means thedialecticbetweenthe text's meaning to the event. Meaning it is supported also by the nature of the genre’s novel.